The Role Of Patience Disposition On The Effect Of Self-Efficacy On Academic Cheating - Fahrul Rozi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research aims to determine the role of the disposition of patience on the effect of self-efficacy on academic cheating. Participants involved in this study were 340 people with 38% women (mean age of all subjects = 19.3 and SD = 2.01). The measuring instrument used to measure the self-efficacy variable is the General Self Efficacy Scale (Schwarzer & Jerusalem, 1995), the patience variable is measured by the First version of the Patience Scale (El Hafiz Lila, Rozi, Ilham, 2013), and the academic cheating variable is measured by the Academic Dishonesty Scale (Bashir & Bala, 2018). The statistical analysis used in this study is the moderating analysis of Process Hayes (2013) which provides an overview of the role of the disposition of patience on the effect of self-efficacy on academic cheating. The disposition of patience will strengthen the negative effect of self-efficacy on academic cheating. The results show that patience acts as a significant moderating variable on the effect of self-efficacy on academic cheating and the disposition of patience strengthens the negative effect between these variables. Where, the negative effect on the effect of self-efficacy on academic cheating depends on the disposition of the level of patience. The higher the disposition of patience, the higher the negative effect of self-efficacy on academic cheating.